(untitled) (American Journal of Pedagogical and Educational Research, 2025)
One of the important conditions for improving the quality of theoretical and methodological training of teachers in pedagogical activity is the systematic unity of general education and special disciplines, which is carried out in interdisciplinary communication. In a number of studies conducted in recent years, the need for an integrated approach to the educational process is noted.